2021
DOI: 10.3389/fphar.2021.632978
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone Improves the All-Cause Mortality and Re-Hospitalization Rates in Acute Myocardial Infarction with Chronic Kidney Disease Patients

Abstract: Background: Mineralocorticoid receptor antagonists (MRA) improve outcomes in chronic kidney disease (CKD) and acute myocardial infarction (AMI) patients. However, the lack of evidence regarding long-term clinical outcomes in the use of MRA, including spironolactone, in patients with AMI combined with CKD.Objectives: This study aimed to investigate whether spironolactone could significantly reduce the risk of all-cause mortality and re-admission in patients with AMI and CKD.Methods: In this single center, obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…For example, Blankenburg et al [ 14 ] presented results for overall CKD, CKD in T2D, as well as CKD (with or without T2D) and HF populations separately, and Tseng et al [ 19 ] reported results for overall CKD, CKD and HF, as well as for CKD and history of CVD. In addition, Qu et al [ 20 ] reported results for overall CKD and CKD in diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Blankenburg et al [ 14 ] presented results for overall CKD, CKD in T2D, as well as CKD (with or without T2D) and HF populations separately, and Tseng et al [ 19 ] reported results for overall CKD, CKD and HF, as well as for CKD and history of CVD. In addition, Qu et al [ 20 ] reported results for overall CKD and CKD in diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…In the Yang et al study [ 26 ], the difference between the incidence of all-cause death in spironolactone users versus non-users was not significant (event rates 64.42 vs. 60.47/1000 person-years, p = 0.432). In the Qu et al [ 20 ] study, spironolactone use was related to significantly lower risk of all-cause mortality compared to standard treatment (HR = 0.389, 95% CI [0.276; 0.548], p < 0.001). Moreover, the reduction in the risk of all-cause mortality in spironolactone users was consistent among analyzed subgroups, including patients with different levels of eGFR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations